UPCRISPR: an ultrafast, one-tube multiplexed nucleic acid detection system for resolving the diagnostic gray zone in HPV16/18 detection - Linlin Bai; Dianwei Liu; Chunyan Qian; Weiqi Yuan; Kaiming Guo; Yao Wang; Feng Qian; Mingmin Shi; Bei Wang; Rui Wang (Analytica Chimica Acta, 2026)

Amplitude-controlled dynamic structural colors on wrinkling surfaces for facile multilevel strain-resolved optical encryption - Dengchong Feng; Shirui Wu; Yuxin Liu; Qi Guo; Rui Chen; Yu Chen; Yuzhao Yang; Haiqiang Wu; Zhiquan Zhao; Shaolin Lu; Zetong Ma; Cheng Wang; et al. (Chemical Engineering Journal, 2026)

Metagenomic insights into Thermus-mediated sulfur oxidation, nitrogen cycling, and thermoadaptation in thermophilic autotrophic denitrification bioreactors - Yuan-Yuan Xu; Xin Tan; Cheng-Cheng Dang; Zhi-Cheng Zhao; Rui Fang; Liang Fan; Nan-Qi Ren; Guo-Jun Xie; Yi-Ning Wu (Bioresource Technology, 2026)

Time-resolved structural remodeling and bioactivity changes of Lentinula edodes polysaccharides during fermentation by Limosilactobacillus fermentum CICC 21828 - Yue Liu; Saiqun Wang; Lu Liu; Zidan Zhao; Rui Cai; Jing Guo; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Bioscience, 2026)

Enhanced SMA friction self-restoring damper (eSMA-FSRD) with leveraged force-displacement control for structural seismic resilience - Maojun Yuan; Lueqin Xu; Rui Jiang; Da Fu; Wei Guo (Engineering Structures, 2026)

Two-phase flow in clayey silt hydrate reservoirs drives migration and clogging of fine clay particles - Jiang Lei; Wei Guo; Yuan Wang; Wen Zhang; Huie Chen; Pengyu Zhang; Rui Jia (Engineering Geology, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Anti-chlorine corrosion strategies and selective oxygen evolution in seawater electrolysis: A review - Chao Guo; Yijie Zhang; Yuan Gao; Rui Yao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

A root cause diagnosis strategy based on error correction instantaneous granger causality algorithm for non-stationary industrial processes - Rui Chen; Yuan-Qiang Zhou; Li-Lan Liu; Jian-Guo Wang; Yuan Yao; Chen Peng (Process Safety and Environmental Protection, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Quantitative source apportionment of soil geochemical elements in a typical mountain-plain transition zone, northern China: the combined influence of geological background and anthropogenic activities - Huan Li; Yi-Xuan Zhang; Yang Yao; Qin-Rui Zhang; Bo Zhang; Yong-Wei Zhao; Bing Han; Guo-Li Yuan (Environmental Geochemistry and Health, 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

A Novel ML–NWP Coupled Optimization Approach on a Reconstructed WRF Model - Hai Chu; Yuan Cao; Rui Wang; Jianming Xu; Lei Chen; Xuliang Fan; Shiqi Chen; Jianhai Guo; Junjing Wu (Journal of Meteorological Research, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Oil Slick Detection in X-Band Marine Radar Imagery: Leveraging a Boundary-Aware SBR Feature and an Improved Whale Optimization Algorithm - Jianxun Rui; Jin Xu; Jianbin Yuan; Zekun Guo; Shuo Zhang; Yiteng Zhang; Qiuyu Fu; Boxi Yao; Yulong Yang; Wenhui Li (Journal of Marine Science and Engineering, 2026)
Marine oil spills pose a persistent threat to marine ecosystems and coastal economies, and their rapid and unpredictable spread requires timely and reliable monitoring. In X-band marine radar images, oil slicks usually appear as low-contrast dark targets embedded in heterogeneous sea clutter, making accurate segmentation particularly challenging. To address this problem, this study proposes a training-free two-stage oil slick detection framework that combines an improved Slick Boundary Ratio (SBR) feature with an improved Whale Optimization Algorithm (WOA). First, the improved SBR feature is used to extract the oil slick region of interest (ROI). Then, the improved WOA is employed to determine the global threshold for oil slick segmentation. Experimental results show that the proposed method achieves accurate and spatially coherent oil slick segmentation in complex radar backgrounds, with an Accuracy of 99.36%, a Precision of 85.73%, a Recall of 84.42%, an F1-score of 85.07%, and an Intersection over Union (IoU) of 74.01%. These results indicate that the proposed framework can effectively suppress false positives while maintaining strong detection sensitivity, thereby improving segmentation robustness in low-contrast marine radar scenes. Owing to its training-free design, the proposed method shows potential for shipborne and coastal oil spill monitoring applications.

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Twelve-year organic substitution fertilization mitigates microbial nutrient limitation and enhances soil carbon pool stability in a rubber plantation - Wenxian Xu; Yingying Zhang; Wenjie Liu; Congju Zhao; Ashar Tahir; Chuan Yang; Xinwei Guo; Rui Sun; Xiangshuai Yan; Huifang Yuan; Qiu Yang; Zhixiang Wu (Plant and Soil, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Wave-absorbing grouting for mitigating rockbursts triggered by multi dynamic disturbances in deep tunnels - Heng-Yuan Zhang; Ben-Guo He; Xiang-Rui Meng; Jia-Hua Guan; Hua-Wei Xu (Tunnelling and Underground Space Technology, 2026)

Aggregation kinetics and stability of Ce(IV)-borate colloid: Effect of pH, electrolytes, gibbsite colloid, and humic acid colloid - Kang Chen; Rui Zhang; Chunsheng Shi; Shanrong Yuan; Zishuo Li; Daming Zhang; Qiang Jin; Zhijun Guo; Zongyuan Chen (Journal of Contaminant Hydrology, 2026)

Tailoring a simplified and steady-state kombucha consortium for newly-formulated kiwifruit beverage production: Impacts on untargeted/targeted metabolites, antioxidant capacities and flavor profiles - Shiqi Li; Keying Chu; Rong Guo; Jiamin Wu; Xingnan Wang; Jing Guo; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2026)

Research on the failure modes of frozen loess under uniaxial compression with varying moisture contents - Yuan Xin; Qiang Sun; Pingye Guo; Jingjing Nan; Jishi Geng; Ziyu Wang; Rui Lv; Shaoli Liu (Journal of Applied Geophysics, 2026)

Synergistic 3d-5d orbital interactions on oxygen vacancy-rich Pt/TiO2 for enhanced photothermal catalytic oxidation of propylene - Xiaoxiao Zhu; Weidong Yuan; Siyi Song; Tong Chen; Wenjun Xiong; Sibo Wang; Jinpeng Hu; Rui Liu; Zhu Luo; Jinlong Wang; Ang Gao; Yanbing Guo (Chemical Engineering Journal, 2026)

An empirical study on the thermal environment improvement and energy conservation of high-reflective-evaporative composite roofs - Lina Jiang; Yunran Min; Jihui Yuan; Chaoqun Zhuang; Rui Guo; Jiayao Yu; Yafeng Gao (Building and Environment, 2026)

Sediment amplifies organic matter cycling and nutrients feedback in eutrophic lake zones - Junfeng Xing; Yuping Zhou; Ding He; Fen Guo; Penghui Li; Yuan Zhang; Rui Lv; Runze Xue; Changqing Liu; Yihua Xiao (Water Research, 2025)

Prevalence and risk factors of Giardia duodenalis in sheep and goats in global: A systematic review and meta-analysis - Zhengyi Li; Wei Wei; Yuan Ma; Luyao Hao; Yuan Guo; Rui Wang (Preventive Veterinary Medicine, 2025)

Genetic sensitivity moderates the effects of joint exposure to air pollution on depression risk: a genome-wide by environment interaction analysis - Yaoyao Sun; Xue Lv; Wenjian Bi; Yuyanan Zhang; Zhe Lu; Jing Guo; Zhewei Kang; Xiaoyang Feng; Yundan Liao; Guorui Zhao; Junyuan Sun; Yang Yang; et al. (Environmental Pollution, 2025)

Wireless gas sensor based on monolayer Ti3C2Tx-modified GaN/CuO heterostructures for ultrafast and trace detection of NO2 gas - Haineng Bai; Cheng Feng; Rui Guo; Yiru Chen; Wenfeng Yuan; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2025)

The synergistic effect of triazine-N and secondary amine-N anchors iodine species with MXene composite cathode for stable aqueous Zn–I2 battery - Jing Ma; Yaoyao Linghu; Kai Yuan; Rui Zhou; Hui Gao; Peihua Zhao; Shaohui Guo; Huiqi Wang; Yongping Qu; Chao Shen; Keyu Xie (Chemical Engineering Journal, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

BaTiO3 dressed in carbon multifunctional layer achieving high areal capacity zinc metal batteries - Rui Wang; Jing Xu; Shijun Luo; Yan Guo; Baohe Yuan; Lei Xu; Junming Li; Yongqi Zhang; Yusheng Wang; Wenpeng Yang; Jinbing Cheng; Yongsong Luo (Chemical Engineering Journal, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

Time-Delayed Rockbursts Induced by Dynamic Disturbances: 793 Cases in Deep Tunnels - Ben-Guo He; Heng-Yuan Zhang; Xia-Ting Feng; Xiang-Rui Meng (Rock Mechanics and Rock Engineering, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Mesoscopic interpretation of fines clogging-induced permeability changes in completely decomposed granite - Rui Chen; Zhi-yuan Luo; Ai-guo Li; Hao Wang; Lei-lei Liu; Liang-liang Zhang (Bulletin of Engineering Geology and the Environment, 2025)

White matter microstructural and cognitive function changes in bipolar depression patients with suicidal ideation - Junfan Liang; Rui Fan; Xinyin Guo; Hua Liu; Xuehua Li; Jixiang Yuan; Kezhi Liu; Xuemei Liang; Bo Xiang (Brain Imaging and Behavior, 2025)

Synergistic reduction of pollutants and GHGs in China's PET industry: A material metabolism perspective - Fu Guo; Rui Li; Yifan Gu; Mingxuan Tuo; Zixin Bian; Yihan Li; Qingbin Yuan; Ming Yang; Yufeng Wu (Resources, Conservation and Recycling, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Immune cell traits and causal relationships with cholecystitis: a mendelian randomization analysis - Ze-fa Xiao; Wei-hao Chai; Xiao-long Shu; Hong-rui Yuan; Fei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

A rapid and nondestructive quantitative detection method for total and organic selenium in selenium-enriched kefir grain based on hyperspectral imaging - Menghui Li; Jinyi Yang; Xing Guo; Rui Sun; Gechao Zhang; Wenhui Liu; Yuanye Liu; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Control, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

Monitoring nutrient and beneficial elements in the topsoil: the function of weathered background and later surficial process on their distribution - Bo Zhang; Kai-Ning Lv; Huan Li; Qin-Rui Zhang; Zhi-Qiang Yin; Wei-Zhi Zhou; Guo-Li Yuan (Environmental Monitoring and Assessment, 2025)

Antagonistic activity of Pochonia chlamydosporia against three helminth eggs and characterization of its serine protease - Luyao Hao; Fengmiao Zhao; Yuan Guo; Yuan Ma; Zhengyi Li; Wen Wang; Hongliang Luo; Rui Wang (Veterinary Parasitology, 2025)

An investigation of the mechanism of emulsion stabilization in octenyl succinic anhydride-modified tamarind seed polysaccharide - Yuxing Kou; Rui Guo; Xianbao Sun; Xuan Ma; Yinan Chen; Lihua Song; Zibo Song; Chunmei Yuan; Siyan Huang; Jian Tang; Yan Wu (Food Hydrocolloids, 2025)

Effect of the Hofmeister series anion salts on the ice recrystallization inhibition activity of tamarind seed polysaccharide - Xianbao Sun; Shihao Dai; Rui Guo; Taijie Zhan; Fan Xie; Yuxing Kou; Xuan Ma; Yinan Chen; Lihua Song; Hui Zhang; Lu Ren; Chunmei Yuan; et al. (Food Hydrocolloids, 2025)

Protective effect of SERCA2a-SUMOylation by SUMO-1 on diabetes-induced atherosclerosis and aortic vascular injury - Jinlin Liu; Shifang Xu; Bin Gao; Meng Yuan; Li Zhong; Rui Guo (Molecular and Cellular Biochemistry, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Assessment of brittle failure in deep tunnels via true triaxial compression - Ben-Guo He; Hong-Pu Li; Xiang-Rui Meng; Si-Yuan Dou; Shengcun Yan; Tao Chen (Tunnelling and Underground Space Technology, 2024)

Reaction mechanism for NH3-SCR of NOx over CrMn1.5O4 catalyst - Zheng-nan Yuan; Rui-tang Guo; Xiao-jing Liu; Yi-feng Xu; Lu Liu; Wei-guo Pan (Fuel, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

A study on the monitoring of landslide deformation disasters in Wenxian County, Longnan City based on different time-series InSAR techniques - Jinlong Zhang; Rui Yang; Yuan Qi; Hui Zhang; Juan Zhang; Qianhong Guo; Chao Ma; Hongwei Wang (Natural Hazards, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Directional synthesis and application of long-chain ethers from biomass-derived carbonyls - Yuan Liu; Fang Liu; Li Yang; Feiqiang Guo; Shiliang Wu; Rui Xiao (Fuel, 2024)

Immobilization of pancreatin based on ultrasound-assisted polydopamine functionalized magnetic porous chitosan for the detoxification of ochratoxin A in wine - Saiqun Wang; Tianmin Guo; Xiaoxue Mei; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Chemistry, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Enhanced efficiency nitrogen fertilizers (EENFs) can reduce nitrous oxide emissions and maintain high grain yields in a rain-fed spring maize cropping system - Yanling Du; Yuan Lu; Shengli Guo; Rui Wang; Xiaotong Song; Xiaotang Ju (Field Crops Research, 2024)

The carbon dots with near-infrared electrochemiluminescence emission and low excitation potential for ultrasensitive analysis of microRNA-222 - Yu-Zhuo Guo; Rui Liu; Ying Zeng; Ye-Yu Liao; Jia-Li Liu; Ya-Qin Chai; Ruo Yuan (Chemical Engineering Journal, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Preparation and application of biocontrol formulation of nematode-trapping fungus-Duddingtonia flagrans - Luyao Hao; Yuan Guo; Xiaomin Wang; Mingjuan Gao; Tonghai Liu; Yuan Ma; Yanni Zhang; Qiannan Li; Rui Wang; Xihuo You (Veterinary Parasitology, 2024)

Carbazomycins I and J, two novel carbazole alkaloids isolated from Saccharopolyspora phattalungensis - Wen Wang; Er Juan Zhao; Ting Peng; Zhang Yuan Yan; Zhi Kai Guo; Rui Hua Jiao (Phytochemistry Letters, 2024)

Retarding ice recrystallization by tamarind seed polysaccharide: Investigation in ice cream mixes and insights from molecular dynamics simulation - Xianbao Sun; Rui Guo; Taijie Zhan; Yuxing Kou; Xuan Ma; Hong Song; Wei Zhou; Lihua Song; Hui Zhang; Fan Xie; Chunmei Yuan; Zibo Song; et al. (Food Hydrocolloids, 2024)

Study on somatic embryogenesis of cinnamomum camphora based on transcriptome sequencing - Yilang Liu; Haoran Guo; Xiaoling Kang; Rui Wu; Meijing Yuan; Li Du (Brazilian Journal of Botany, 2024)

Eco-driving strategy for connected electric buses at the signalized intersection with a station - Yali Zhang; Rui Fu; Yingshi Guo; Wei Yuan (Transportation Research Part D: Transport and Environment, 2024)

Arbuscular mycorrhizal fungi offset NH3 emissions in temperate meadow soil under simulated warming and nitrogen deposition - Nan Cui; Stavros Veresoglou; Yibo Tian; Rui Guo; Lei Zhang; Li Jiang; Furong Kang; Weizhe Yuan; Dan Hou; Lianxuan Shi; Jixun Guo; Mingzhou Sun; et al. (Journal of Environmental Management, 2024)

Inactivation activity and mechanism of pulsed light against Alicyclobacillus acidoterrestris vegetative cells and spores in concentrated apple juice - Rui Cai; Yali Ma; Zhouli Wang; Yahong Yuan; Hong Guo; Qinglin Sheng; Tianli Yue (International Journal of Food Microbiology, 2024)

Relationship between somatic embryogenesis and endogenous hormones of Cinnamomum camphora L. - Haoran Guo; Xiaoling Kang; Meijing Yuan; Rui Wu; Li Du (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Dietary supplementation with polysaccharides from Rhizoma dioscoreae resulting in the enhanced immunity and the structural modulation of the intestinal microbiota in Luciobarbus capito - Yuan Sun; Xiaowei Hu; Xianwei Meng; Rui Liu; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Liang Luo (Aquaculture, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Heavy metal pollution alters reproductive performance and mate choice in an anuran, Strauchbufo raddei - Rui Su; Rui Guo; Zhenyu Liu; Yongna Yuan; Wenya Zhang (Marine Pollution Bulletin, 2023)

Lateral flow immunoassay based on gold nanoparticles for rapid and sensitive detection of zoxamide in grape, tomato and cucumber samples - Yuan Cheng; Aihong Wu; Lingling Guo; Maozhong Sun; Rui Gao; Hua Kuang; Chuanlai Xu; Liguang Xu (Food Chemistry, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Predictive value of serum proteomic biomarkers for noise-induced hearing loss - Yuqiang Lun; Jiawei Chen; Peiheng Lu; Hao Yuan; Pengwei Ma; Weilong Wang; Rui Liang; Siyu Li; Wei Gao; Xuerui Ding; Zi Wang; Jianing Guo; et al. (Environmental Science and Pollution Research, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Driving forces and variation in water footprint before and after the COVID-19 lockdown in Fujian Province of China - Fan Yu; Yuan Wang; Xin Liu; Jinru Yu; Dandan Zhao; Haijun Deng; Bin Guo; Rui Shi; Bowei Wu; Huayang Chen (Journal of Cleaner Production, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Genome-wide identification and expression analysis of the cotton patatin-related phospholipase A genes and response to stress tolerance - Yunxiao Wei; Zhili Chong; Chao Lu; Kaili Li; Chengzhen Liang; Zhigang Meng; Yuan Wang; Sandui Guo; Liangrong He; Rui Zhang (Planta, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Spatial distribution and quantitative source identification of nutrients and beneficial elements in the soil of a typical suburban area, Beijing - Qin-Rui Zhang; Sheng-Qiang Zhang; Yong Huang; Huan Li; Yan-Hui Jia; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Longitalea arenae gen. nov., sp. nov. and Longitalea luteola sp. nov., two new members of the family Chitinophagaceae isolated from desert soil - Shuai Li; Lei Dong; Jia-Rui Han; Guo-Yuan Shi; Chun-Yan Lu; Lu Xu; Wen-Hui Lian; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Wen-Jun Li (Archives of Microbiology, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

A point cloud registration method based on dual quaternion description with point-linear feature constraints - Raobo Li; Xiping Yuan; Shu Gan; Rui Bi; Yan Guo; Sha Gao (International Journal of Remote Sensing, 2022)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

Identification and monitoring landslides in Longitudinal Range-Gorge Region with InSAR fusion integrated visibility analysis - Rui Guo; Sumin LI; Ya’nan Chen; Xiangxin Li; Liwei Yuan (Landslides, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Multifractal characteristics and spatial variability of soil particle-size distribution in different land use patterns in a small catchment of the Three Gorges Reservoir Region, China - Tai-li Chen; Zhong-lin Shi; An-bang Wen; Dong-chun Yan; Jin Guo; Jia-cun Chen; Yuan Liu; Rui-yin Chen (Journal of Mountain Science, 2021)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Metabolomics reveals the drought-tolerance mechanism in wild soybean (Glycine soja) - Xiaoxia Wang; Rui Guo; Mingxia Li; Yuan Liu; Mingli Zhao; Hui Fu; Xueying Liu; Shiyao Wang; Lianxuan Shi (Acta Physiologiae Plantarum, 2019)

Numerical Simulations of Wave-Induced Soil Erosion in Silty Sand Seabeds - Zhen Guo; Wenjie Zhou; Congbo Zhu; Feng Yuan; Shengjie Rui (Journal of Marine Science and Engineering, 2019)
Silty sand is a kind of typical marine sediment that is widely distributed in the offshore areas of East China. It has been found that under continuous actions of wave pressure, a mass of fine particles will gradually rise up to the surface of silty sand seabeds, i.e., the phenomenon called wave-induced soil erosion. This is thought to be due to the seepage flow caused by the pore-pressure accumulation within the seabed. In this paper, a kind of three-phase soil model (soil skeleton, pore fluid, and fluidized soil particles) is established to simulate the process of wave-induced soil erosion. In the simulations, the analytical solution for wave-induced pore-pressure accumulation was used, and Darcy flow law, mass conservation, and generation equations were coupled. Then, the time characteristics of wave-induced soil erosion in the seabed were studied, especially for the effects of wave height, wave period, and critical concentration of fluidized particles. It can be concluded that the most significant soil erosion under wave actions appears at the shallow seabed. With the increases of wave height and critical concentration of fluidized particles, the soil erosion rate and erosion degree increase obviously, and there exists a particular wave period that will lead to the most severe and the fastest rate of soil erosion in the seabed.

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Composition of stable isotope in precipitation and its influences by different vapor sources in the eastern Qilian Mountains - Wen-xiong Jia; Xing-gang Ma; Xiu-ting Xu; Rui-feng Yuan; Dan Ding; Guo-feng Zhu (Journal of Mountain Science, 2018)

Structural Strength Analysis of a Tri-Floater Floating Foundation for Offshore VAWT - Liqin Liu; Haixiang Zhao; Wanhai Xu; Rui Yuan; Ying Guo (Journal of Ocean University of China, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Increased lateral root formation by CRISPR/Cas9-mediated editing of arginase genes in cotton - Yanling Wang; Zhigang Meng; Chengzhen Liang; Zhaohong Meng; Yuan Wang; Guoqing Sun; Tao Zhu; Yongping Cai; Sandui Guo; Rui Zhang; Yi Lin (Science China Life Sciences, 2017)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

Characterization of Flavor Properties from Fish ( Collichthys niveatus ) Through Enzymatic Hydrolysis and the Maillard Reaction - Qiaoling Zhao; Qing Shen; Rui Guo; Jiajia Wu; Zhi-yuan Dai (Journal of Aquatic Food Product Technology, 2016)

Effects of induced pluripotent stem cells-derived conditioned medium on the proliferation and anti-apoptosis of human adipose-derived stem cells - Rui-Ling Lian; Xiao-Ling Guo; Jian-Su Chen; Yong-Long Guo; Jia-Fu Zheng; Yuan-Wen Chen (Molecular and Cellular Biochemistry, 2016)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

Regulation of three isoforms of SOD gene by environmental stresses in citrus red mite, Panonychus citri - Ying-Cai Feng; Chong-Yu Liao; Wen-Kai Xia; Xuan-Zhao Jiang; Feng Shang; Guo-Rui Yuan; Jin-Jun Wang (Experimental and Applied Acarology, 2015)

Preparation of malathion MIP-SPE and its application in environmental analysis - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Lei Shi; Ming Xing; Ping Guo; Yuan Ding; Hong Yang (Environmental Monitoring and Assessment, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Gene transcript profiles of the TIA biosynthetic pathway in response to ethylene and copper reveal their interactive role in modulating TIA biosynthesis in Catharanthus roseus - Ya-Jie Pan; Jia Liu; Xiao-Rui Guo; Yuan-Gang Zu; Zhong-Hua Tang (Protoplasma, 2015)

Genome-Wide Identification, Expression, and Activity Analysis of Alkaline/Neutral Invertase Gene Family from Cassava (Manihot esculenta Crantz) - Yuan Yao; Meng-Ting Geng; Xiao-Hui Wu; Jiao Liu; Rui-Mei Li; Xin-Wen Hu; Jian-Chun Guo (Plant Molecular Biology Reporter, 2015)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Expression and Clinical Significance of CK19 and CK20 Expressions in Transverse Mesocolon Biopsies from Patients with Gastric Carcinoma - Guo-Rui Sun; Xiao-Yuan Dong; Qing-Si He; Hui Qu; Yan-Min Wang (Cell Biochemistry and Biophysics, 2012)

Physiological responses of Catharanthus roseus to different nitrogen forms - Xiao-Rui Guo; Yuan-Gang Zu; Zhong-Hua Tang (Acta Physiologiae Plantarum, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Characterization of a novel isoform of the human ORMDL3 gene - Rui Jin; Wen-Xiao Yuan; Hua-Guo Xu; Wei Ren; Li-Li Zhuang; Guo-Ping Zhou (Cell and Tissue Research, 2011)

Organochlorine pesticides in the soil of a karst cave in Guilin, China - Yinghui Wang; Songjun Guo; Rui Xue; Shihua Qi; Yiyin Xu; Baoming Xue; Daoxian Yuan (Environmental Monitoring and Assessment, 2011)

Comparative ecophysiological responses to drought of two shrub and four tree species from karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Guo-Qing Li; Yuan-Run Zheng; Li-Fei Yu; Rui Yang (Trees, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Targeting interleukin-21 in rheumatoid arthritis - Feng-Lai Yuan; Wei Hu; Wei-Guo Lu; Xia Li; Jian-Ping Li; Rui-Sheng Xu; Cheng-Wan Li; Fei-Hu Chen; Cheng Jin (Molecular Biology Reports, 2011)

Comparison of sociability, parental care and central estrogen receptor alpha expression between two populations of mandarin voles (Microtus mandarinus) - Ruiyong Wu; Aifang Yuan; Qinwei Yuan; Rui Guo; Fadao Tai; Zhenzhen Song; Chengjun Yu (Journal of Comparative Physiology A, 2011)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Genetic characterization of ticks from southwestern Romania by sequences of mitochondrial cox1 and nad5 genes - Lidia Chitimia; Rui-Qing Lin; Iustin Cosoroaba; Xiang-Yun Wu; Hui-Qun Song; Zi-Guo Yuan; Xing-Quan Zhu (Experimental and Applied Acarology, 2010)

A PKC-β inhibitor protects against cardiac microvascular ischemia reperfusion injury in diabetic rats - Liping Wei; Dongdong Sun; Zhiyong Yin; Yuan Yuan; Andrew Hwang; Yingmei Zhang; Rui Si; Rongqing Zhang; Wenyi Guo; Feng Cao; Haichang Wang (Apoptosis, 2010)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Effects of Neuregulin on Expression of MMP-9 and NSE in Brain of Ischemia/Reperfusion Rat - Qin Li; Rui Zhang; Yin-lin Ge; Yuan-wu Mei; Yun-liang Guo (Journal of Molecular Neuroscience, 2009)

Effect of Neuregulin on Apoptosis and Expressions of STAT3 and GFAP in Rats Following Cerebral Ischemic Reperfusion - Qin Li; Rui Zhang; Yun-liang Guo; Yuan-wu Mei (Journal of Molecular Neuroscience, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

A new linearly-combined bi-exponential model for kinetic analysis of the isometric relaxation process of Bufo gastrocnemius under electric stimulation in vitro - Rui Guo; Sheng-bing Li; Li-na Zhao; Yun-sheng Zhao; Wei Lu; Pei Yuan; Ping Deng; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2007)

Double-strand hydrolysis of DNA by a magnesium(II) complex with diethylenetriamine - Pin Yang; Rui Ren; Maolin Guo; Aixin Song; Xiangli Meng; Caixia Yuan; Qinghua Zhou; Huili Chen; Zhenhai Xiong; Xiaoli Gao (JBIC Journal of Biological Inorganic Chemistry, 2004)